Peran dan Kendala Perempuan Tradisional Mentawai dalam Pengembangan Desa Wisata Muntei Kecamatan Siberut Selatan - Vinsensia Salakkokoai (Journal of Tourism Sciences, Technology and Industry, 2026)
Muntei Village in South Siberut District, Mentawai Islands Regency, won first place in the Visitor Attraction category of the Indonesian Village Tourism Award (ADWI) 2023. Behind this achievement, traditional women who daily preserve the authentic culture of Mentawai have never been specifically studied regarding their roles and constraints in tourism development. This study aims to describe the roles of traditional women in developing Muntei Village Tourism and to identify the constraints they face in empowerment. The research uses a qualitative descriptive method with data collection through semi-structured interviews, observation, and documentation of 16 informants selected by purposive sampling. The results show that traditional women carry out six roles in tourism: providing traditional culinary for tourists, managing homestays, performing cultural attractions through sanggar, producing and selling manik-manik crafts, preserving traditional rituals, and participating in Pokdarwis structure. A distinctive pattern was found: women only participate when called upon, never on their own initiative. The constraints found are multilayered, covering structural dimensions (limited access to relevant training and capital), cultural dimensions (double burden and customary habits), and institutional dimensions (unequal distribution of benefits). This research concludes that inclusive and gender-equitable tourism development in Muntei Village requires planned intervention from all stakeholders.Keywords:traditional women, village tourism, Mentawai, women empowerment, cultural tourism